OPTIMASI RANCANG BANGUN PROTOTYPE KINCIR AIR KAPASITAS 100 WATT - Budi Hartadi; Yassyir Maulana (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
Water is a source of energy that cheap an relatively were easily obtained, because the water is potential energy (on watel falling in) and their kinetic energy on running water. This energy could be converted into a source of energy that can produce electricity. The purpose of this research is to design form prototype of waterwheel based on the speed of water flow obtained from a barabai river in Kabupaten Hulu Sungai Selatan Province of South Kalimantan. The methodology used in research is quantitative methods and experimental methods. The research known the speed of water flow in Barabai river is 1 m/s, discharge of water is 0,00204 m3/s and water power is 1.020 Watt. While from the prototype waterwheel obtained the waterwheel round by 181 rpm, torque of waterwheel is 0,0088 Nm and the power of waterwheel is 167 Watt. From the result of research can inconclusive if the waterwheel scale inlarged, so the power of waterwheel will be increase.Keyword : The Prototype of WaterWhell, Round of Shaft, The Power of Waterwheel